Human leukocyte antigen class II expression is a good prognostic factor in adult T-cell leukemia/lymphoma - Mai Takeuchi; Hiroaki Miyoshi; Naoko Asano; Noriaki Yoshida; Kyohei Yamada; Eriko Yanagida; Mayuko Moritsubo; Michiko Nakata; Takeshi Umeno; Takaharu Suzuki; Satoru Komaki; Hiroko Muta; et al. (Haematologica, 2019)
Attenuated human leukocyte antigen (HLA) class I expression is implicated as a major immune escape mechanism in several types of tumor. We previously reported that HLA class I/β2 microglobulin and programmed death ligand-1 expression are prognostic factors in adult T-cell leukemia/lymphoma. A recent report suggested that HLA class II expression is also an important prognostic factor for the clinical outcome of programmed death-1 blockade therapy in recurrent/refractory Hodgkin lymphoma. This prompted us to evaluate HLA class II expression in adult T-cell leukemia/lymphoma and to compare the findings with the patients’ clinicopathological features. Of the 132 biopsy specimens examined from newly diagnosed patients, lymphoma cells were positive for HLA class II expression in 44 patients (33.3%), whereas programmed death ligand-1 expression was observed on neoplastic cells from nine patients (6.9%) and on stromal cells in the tumor microenvironment in 83 cases (62.9%). HLA class II-positive cases showed a significantly better overall survival compared to the HLA class II-negative cases (P